RANCANG BANGUN SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT PADA KULIT DENGAN METODE FOWARD CHAINING - Lisnauli Saragih; Mariska Putri Pratiwi (LPPM Universitas Putera Batam, 2025)
This study aims to develop an artificial intelligence-based expert system to help diagnose skin diseases. This system is designed to help users, especially the general public, identify the type of skin disease based on the symptoms they experience. By collecting data from dermatologists and medical literature, this system is built using the forward chaining method. The system's knowledge base contains rules that link symptoms to certain skin diseases. System testing shows high accuracy in diagnosing various types of skin diseases, such as psoriasis, eczema, and fungal infections. With this expert system, it is expected to increase public access to skin health information and help early detection of skin diseases.